Pengembangan Sistem Informasi Eksekutif Dashboard E-Government Berbasis Website Menggunakan Metode Rational Unified Process (Studi Kasus: Dinas Komunikasi dan Informatika Kabupaten Sidoarjo) - Yusuf Kurniawan; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Department of Communication and Informatics of Sidoarjo Regency was given authority by the Regent Regulation Number 46 the year 2018 to become a GCIO (Government Chief Information Officer) who has the task of assisting the Regent one of them in managing the government data. Construction of Data Warehouse to fulfill the needs of the regent will government data still felt less because the data stored cannot be presented and the regent still relies on the old system that takes quite a long time. Based on the problem, an executive information system of Dashboard E-Government based website to meet the needs of the regent in accessing the government data from the data warehouse that has been processed and presented automatically by the system. Development of this system using the rational method Unified Process. Research has been conducted to produce an analysis of needs, system design, implementation and testing of systems. System tested using several testing methods namely validation testing, compatibility testing, and user acceptance testing. The test results of this system indicate that the system is running well in accordance with the requirements that have been made and make it easier for the Bupati to access government data and follow up on the data that has been presented on the e-Government dashboard executive information system.